Situational (in)consistency in learning strategies - Mujagić, Amela (Array, 2012)
Following theoretical assumptions on situational specificity of learning process, and the criticism of the existing self-report questionnaire measures as a means for capturing the learning dynamics, this study aims to examine the amounts of variance in learning strategies that might be attributed to stable individual differences on the one hand, and to more transient contextual or situational factors on the other. Data on learning strategies used while preparing for written exams were collected from 155 second year university students on two occasions with seven weeks time lag. Consistency and situational specificity of learning strategies were tested within the context of latent statetrait theory. The results revealed that while all learning strategies are affected by situational factors, some of them are used more consistently in two learning situations by students (organization, elaboration, and critical reasoning) than others (rehearsal and metacognitive strategies). The results also suggest that self-report measures of learning strategies, contextualized on course level, can capture variability in learning strategies deployment across different occasions.